Biobased Spiroimides from Itaconic Acid and Formamides: Molecular Targets for a Novel Synthetic Application of Renewable Chemicals - Hornink, Milene Macedo; Lopes, Alice Uva; Andrade, Leandro Helgueira (Synthesis, 2020)
Spiroimides exhibit a wide range of biological activities, such as anticonvulsant, antiarrhythmic, and antihyperglycemic activities. Herein, a novel synthetic application of renewable chemicals, itaconic acid and formamides, is described. Proper exploitation of the reactivity of itaconic acid and formamide allows for the development of an efficient synthetic approach for the production of several new biobased spiroimides, spiro[dihydroquinolin-2-one-succinimides] and spiro[indolin-2-one-glutarimides], in excellent overall yields (up to 98%).
Keywords: spiroimides; itaconic acid; formamides; renewable building blocks; photochemistry